Factors affecting variability in infiltration of ambient particle and gaseous pollutants into home at urban environment. (December 2021) - Hossain, Md Shakhaoat; Che, Wenwei; Frey, H. Christopher; Lau, Alexis K.H.
Abstract: The majority of urban residents live in places with air quality exceeding World Health Organization guidelines. To quantify infiltration of outdoor pollution, and key factors affecting it, common outdoor air pollutants (PM2.5, NO2, and O3 ) were measured at 49 homes in Hong Kong. Infiltration factors (Finf ) were derived based on linear regression of simultaneous indoor and outdoor measurements for each pollutant at each home. Finf estimated based on data for home occupancy, during which people were actually exposed, differed by up to 22%, 73% and 63% for PM2.5, NO2 and O3, respectively, from estimates based on whole monitoring data. This indicates the importance of separating occupancy time to quantify Finf for exposure estimation. The inter-home variability in occupancy Finf ranged from 0.11 to 1.00 (mean: 0.75) for PM2.5, 0.14 to 1.00 (mean: 0.53) for NO2, and 0.05 to 0.95 (mean: 0.47) for O3 . Ventilation practices (e.g., window opening duration and air-conditioning on/off) explained 48%, 20%, and 10% of the inter-home variations in PM2.5, NO2 and O3 Finf, respectively. Use of air purifiers explained an additional 8%–9% of variations for PM2.5 and NO2 . Thus, there is potential to reduce outdoor infiltration by modifying occupant behaviours. Compared to PM2.5 (R 2 = 0.63), the developed models explained less variability in Finf for NO2 (R 2 = 0.40) and O3 (R 2 = 0.10). These two gases are chemically reactive. Further investigation, supported by additional measurements of related chemical species, is needed to improve understanding of infiltration process of reactive gases such as NO2 and O3 . Graphical abstract: Image 1 Highlights: Outdoor infiltration for PM2.5, NO2 and O3 were quantified in 49 homes. Separation of occupancy and non-occupancy improved accuracy of infiltration estimation. Outdoor infiltration varied by a factor of 9, 7 and 19 for PM2.5, NO2 and O3 among homes. Ventilation, use of air conditioner and purifier were dominant predictors for infiltration. Identified predictors may serve as intervention to reduce concentrations at home.